Studies on chemically deposited copper tin sulphide thin films: EDX and SEM investigations - Ho, Soon Min (2017)
Chemical bath deposited copper tin sulphide thin films on indium doped tin oxide glass substrate from copper sulfate, tin chloride and sodium thiosulfate have been studied in this work. The obtained films were characterized using scanning electron microscopy and energy dispersive analysis X-ray technique. The scanning electron microscopy studies indicate that larger grains could be observed for the films prepared by using higher concentration of tin chloride.